Testing the conventional and Islamic financial market contagion: evidence from wavelet analysis - Saiti, Buerhan; Bacha, Obiyathulla Ismath; Masih, Mansur (Taylor & Francis, 2016)
This study is a first attempt at testing the extent of contagion for conventional and Shari’ahcompliant stock indices. We examine the period surrounding the U.S. subprime crisis of 2007–9 and the Lehman Brothers collapse of 2008 to determine the relative extent of contagion. We find no clear evidence of contagion during the subprime crisis however, during the Lehman collapse most conventional indices showed contagion. Interestingly, the Shariah-compliant indices mostly do not show evidence of contagion. 10 Collectively, our results have important implications for fund managers in terms of asset allocation risk and policymakers seeking an optimal policy response to crises.